ナンキョク エンガンイキ デノ ブラックカーボン キセツ ヘンカ ト ユソウ カテイ - 原, 圭一郎; ハラ, ケイイチロウ; 長田, 和雄; オサダ, カズオ; 矢吹, 正教; ヤブキ, マサノリ; 林, 政彦; ハヤシ, マサヒコ; 山内, 恭; ヤマノウチ, タカシ; 塩原, 匡貴; シオバラ, マサタカ; et al. (2010)
P(論文) 2004年2月～ 2007年1月(JARE-45～ JARE-47)に南極昭和基地で,大気中ブラックカーボン(BC)の連続観測を実施した.昭和基地での観測期間中のBC濃度範囲は,検出下限～ 176 ng m^3 だった.4-10月には,低気圧の接近やブロッキング現象による中緯度から極域に向けた空気塊の流入により,BC濃度の増加が頻繁に観測された.BC濃度の高い空気塊は,大西洋やインド洋から対流圏下部経由で南極沿岸域である昭和基地へ輸送されていた.夏季(11-2月)に,BC濃度は地上風速と共に日変化を示し,大陸から吹き下りるカタバ風内でBC濃度が増加していた.南極大陸内でのBCソース強度は低いため,大陸上の大気(カタバ風)中のBCは,低中緯度から自由対流圏経由で南極域へ長距離輸送されていると考えられる.昭和基地でのBC濃度季節変化は,7-8月に極大を示していたが,他の南極沿岸基地(Halley, Neumayer, and Ferraz)や大陸上の基地(Amundsen-Scott)では,10月に極大をとっていた.この違いは,輸送経路,重要なBC発生地域,輸送中の降水によるBCの除去過程の違いによると考えられる. Measurement of atmospheric black carbon (BC) was carried out at Syowa Station Antarctica (69゜00′S, 39゜35′E) from February 2004 until January 2007. The BC concentration at Syowa Station ranged from below detection to 176 ng m^<-3>. Higher BC concentrations were observed frequently from April until October. Increase of BC concentration may be associated with poleward flow due to the approach of a cyclone and or blocking event during winter-spring. The BC-rich air masses traveled through the lower troposphere from the Atlantic and Indian Oceans to Syowa (Antarctic coast). During the summer (November-February), the BC concentration showed a diurnal variation together with surface wind speed and increased in the presence of katabatic wind from the Antarctic continent. Considering the low BC source strength over the Antarctic continent, the higher BC concentration in the continental air (katabatic wind) might be caused by long range transport of BC via the free troposphere from mid- and low- latitudes. The seasonal variation of BC at Syowa Station had a maximum in July-September, while at the other coastal stations (Halley, Neumayer, and Ferraz) and a continental station (Amundsen-Scott), the maximum occurred in October. This difference may result from different transport pathways, significant contribution of source regions and scavenging of BC by precipitation during the transport from the source regions. During the austral summer, long-range transport of BC via the free troposphere is likely to ...